2023
DOI: 10.1242/dev.201450
|View full text |Cite
|
Sign up to set email alerts
|

BMP4 triggers regulatory circuits specifying the cardiac mesoderm lineage

Abstract: Cardiac lineage specification in the mouse is controlled by TGFβ and WNT signaling. From fly to fish, BMP has been identified as indispensable heart inducer. A detailed analysis of the role of Bmp4 and its effectors Smad1/5, however, were still missing. We show that Bmp4 induces cardiac mesoderm formation in murine ESCs in vitro. Bmp4 first activates Wnt3 and up-regulates Nodal. pSmad1/5 and the WNT effector Tcf3 form a complex, and together with pSmad2/3 activate mesoderm enhancers and Eomes. They then cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…During development, SOX2 antagonizes and inhibits expression of the ME TFs Eomes and T ( Koch et al., 2017 ; Blassberg et al., 2022 ; Wang et al., 2012 ; Thomson et al., 2011 ). We recently showed that ME TFs induce differentiation by activating ME enhancers via increasing their accessibility ( Tsaytler et al., 2023 ). We hypothesized that opening of DARs in SOX2 KO cells may be mediated by ME TFs and analyzed the binding of pSMAD1/5, pSMAD2, EOMES, and T to these DARs in ME cells ( Figures S1 D and S1E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During development, SOX2 antagonizes and inhibits expression of the ME TFs Eomes and T ( Koch et al., 2017 ; Blassberg et al., 2022 ; Wang et al., 2012 ; Thomson et al., 2011 ). We recently showed that ME TFs induce differentiation by activating ME enhancers via increasing their accessibility ( Tsaytler et al., 2023 ). We hypothesized that opening of DARs in SOX2 KO cells may be mediated by ME TFs and analyzed the binding of pSMAD1/5, pSMAD2, EOMES, and T to these DARs in ME cells ( Figures S1 D and S1E).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that during BMP4-induced ME differentiation, Sox2 is repressed by mesodermal TFs, and neural fate genes are not expressed during the differentiation course ( Tsaytler et al., 2023 ). At early stages of WT ESC differentiation, Sox2 repression is mediated by SMAD4, whereas loss of Smad4 results in rapid up-regulation of neural fate genes in BMP4-treated cells despite the absence of NE inducers ( Tsaytler et al., 2023 ). Here, we showed that SOX2 ablation in ESCs leads to opening of enhancers bound by ME TFs ( Figures S1 D–S1F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These directly activate the primary cardiac mesoderm regulator, mesoderm posterior BHLH transcription factor 1 (Mesp1) [ 20 , 21 ], and the family member Mesp2 [ 22 ]. This mechanism is reinforced by the activation of TGF-β superfamily signaling by Nodal and BMP4 (bone morphogenetic protein 4) agonists [ 23 , 24 ]. Together with Mesp1/2, Nodal and BMP4 induce the expression of the platelet-derived growth factor receptor-α (Pdgfr-α), which can be used to effectively monitor the emergence of cardiovascular mesoderm [ 25 ].…”
Section: Genesis Of San: Molecular Determinantsmentioning
confidence: 99%
“…DKK1, which subsequently inhibits Wnt/β-catenin signaling, converts the anterior mesoderm into a cardiogenic mesoderm ( Figure 1 ) [ 20 , 21 , 26 ]. Together with Wnt/β-catenin signaling inhibition, BMP4 and the fibroblast growth factor (FGF) support cardiac mesoderm formation [ 23 , 27 ]. In the posterior component, where Wnt/β-catenin signaling is still active and notochord (axial mesoderm)-released Noggin inhibits BMP4, the lateral plate mesoderm becomes the hemangiogenic mesoderm [ 28 , 29 ].…”
Section: Genesis Of San: Molecular Determinantsmentioning
confidence: 99%